Food related: an artistic approach towards knowledge sharing - Klaveren, Rosanne van (DEU, 2019)
Artistic participatory practices can establish connections between people(s) that are valuable for the sharing of knowledge. In this article, I explain from my research practice how an artistic approach can stimulate, structure and enrich knowledge sharing. During my doctoral research at KU Leuven in Belgium, a prototype of an expressive space was designed to collect, map and exchange facts and experiences related to Arctic food culture: the Food Related platform. Decisions that I made and strategies that I used during this project are reviewed while focusing on two topics: 1) food as a subject and stimulus for sharing, 2) the use of creative questionnaires and cultural probes as a method to include imagination. Empirical findings give insight in my experiences and approaches as an artist, which I believe can be inspirational for knowledge sharing projects beyond the field of art.